(untitled) - Owen-Smith, R. Norman (Malden, MA, 2007)
This book provides students with the skills to develop their own models for application in conservation biology and wildlife management. Assuming no special mathematical expertise, the computational models used are kept simple and show how to develop models in both spreadsheet and programming language format. Develops thought-provoking applications which emphasize the value of modeling as a learning tool. Examines basic descriptive equations, matrix representations, consumer-resources interactions, applications in simulation, scenarios, harvesting, population viability, metapopulation dynamics, disease outbreaks, vegetation stage and state dynamics, habitat suitability assessment, and model selection statistics. Includes a wide range of examples relating to birds, fish, plants and large African mammals.
Keywords: Conservation biology,Wildlife management,Bảo tồn sinh vật,Quản lý động vật hoang dã; Computer simulation,Computer simulation,Mô phỏng máy tính,Mô phỏng máy tính